2017
DOI: 10.18632/oncotarget.15302
|View full text |Cite
|
Sign up to set email alerts
|

Precursor N-cadherin mediates glial cell line-derived neurotrophic factor-promoted human malignant glioma

Abstract: As the most prevalent primary brain tumor, gliomas are highly metastatic, invasive and are characteristic of high levels of glial cell-line derived neurotrophic factor (GDNF). GDNF is an important factor for invasive glioma cell growth; however, the underlying mechanism involved is unclear. In this study, we affirm a significantly higher expression of the precursor of N-cadherin (proN-cadherin) in most gliomas compared with normal brain tissues. Our findings reveal that GDNF interacts with the extracellular do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 35 publications
4
25
0
Order By: Relevance
“…The GO analysis identified target genes involved in transcription regulation, signal transduction, cell adhesion, cell cycle, cell differentiation, and anti-apoptosis, all functions closely related to glioma development [38]. Recent studies have reported that precursor N-cadherin and integrin β1 proteins serve as signal transduction molecules in GDNF-induced glioma migration [13, 39]. These cell adhesion molecules are associated with 5 miRNAs, namely hsa-miR-183-5p, hsa-miR-205-5p, hsa-miR-152-3p, hsa-miR-629-5p, and hsa-miR-3609.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GO analysis identified target genes involved in transcription regulation, signal transduction, cell adhesion, cell cycle, cell differentiation, and anti-apoptosis, all functions closely related to glioma development [38]. Recent studies have reported that precursor N-cadherin and integrin β1 proteins serve as signal transduction molecules in GDNF-induced glioma migration [13, 39]. These cell adhesion molecules are associated with 5 miRNAs, namely hsa-miR-183-5p, hsa-miR-205-5p, hsa-miR-152-3p, hsa-miR-629-5p, and hsa-miR-3609.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the increase positively correlated with pathological tumor grade [10]. Subsequent research revealed that GDNF strongly induces glioma cell proliferation and migration [11-13]. Knocking down expression of GDNF or its receptor GDNF family receptor α1 (GFRα1) effectively inhibits the pathological progression of glioma [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Maret et al (11) reported that the precursors of N-cadherin (proN-cadherin) and N-cadherin were present on the cell membrane and the proportion of precursors on the tumor cells was higher (11). Our previous study doubted recent studies on N-cadherin, criticizing that these studies were actually about precursors of N-cadherin, and we demonstrated that GDNF can promote the adhesion of glioma cells to the matrix by promoting the expression of proN-cadherin in glioma cells, which successively amplified the process of migration and invasion (2).…”
Section: Introductionmentioning
confidence: 53%
“…In recent years, a deeper understanding of the molecular mechanism underlying glioma development has led to the discovery of many molecular markers as indicators of clinical diagnosis and treatment. Among them are adhesion molecules involved in the migration and metastasis of gliomas (2), which are mostly clinically applied (3). However, little is known about the effect of adhesion molecules on the proliferation of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation